Menopause-related symptoms and symptom management of women in Manila - Mendoza, Ann Morrich M.; Macatangay, Nathaniel Bernard B.; Mahilum, Ella Mae Lolith P.; Mauleon, Lyka Monique G.; Mejia, Robert L.; Mendoza, Michelle Rose R.; Mercado, Carmela Louise C.; Victoria, Alexia Leigh D. (Manila College of Nursing University of the Philippines Manila, 2018)
Millions of women experience the symptoms of menopause as they reach middle
adulthood and are subjected to the consequences of decreased estrogen levels in the body.
In the Philippines, the topic of menopause is slowly being given more attention on the
population ages over the next few decades. This study (1) described the commonly-
reported menopause-related symptoms (MRS) across stages of reproductive aging; (2)
determined the level of bothersomeness of MRS; (3) determined the knowledge of
women on menopause; (4) determined the relationship between knowledge and
bothersomeness of MRS; and (5) determined the practices of women in managing their
symptoms.

This study was descriptive correlational in nature. Through purposive sampling,
the researchers were able to gather 400 participants within the six (6) districts of Manila
based on the following inclusion criteria: (1) women aged 35-50 years, and (2) living and
working in Manila. Women with artificial menopause and (2) those who have known
medical diseases such as thyroid diseases and polycystic ovarian syndrome were
excluded. Self-administered questionnaire adapted from several studies and tools was
utilized to gather data.

Results of the study showed that the mean age of menopausal women is 48.67 ±
1.88 years; much later than what was known in 1994 which is at 48 years. However,
compared to other Asian women, it is earlier as their age of menopause is 51 years. It
was also found that the participants reported lesser symptoms than Western women,
however, mean number of MRS reported by the participants is increasing across stages of
reproductive aging. It revealed that the most frequently reported MRS were aching of
muscles and joints (62.75%), sweating (61.5%), and hot flushes (59.25%). These
symptoms reported were concurrent with the symptomatology of Asian women.

Overall, participants perceived MRS as mildly bothersome. Though, the
bothersomeness of vasomotor, emotional, physical, and sexual symptoms showed an
increasing trend across stages of reproductive aging.

As a woman progresses through the stages of reproductive aging, there is an
increasing trend in knowledge scores from premenopausal to early postmenopausal with
a slight decrease in the late postmenopause. In terms of knowledge scores and level of
bothersomeness, it showed that- knowledge is a significant factor only in emotional
domain as certain studies show that decreased knowledge on menopause actual leads to
lesser coping abilities. In terms of practices related to MRS, participants mostly reported
self-care actions such as taking frequent baths (62%) for vasomotor symptoms, use of
diversional activities (58.50%) for emotional symptoms, rest (82.25%) for physical
symptoms, and most of the women do not manage (31.25%) sexual symptoms, and only a
few (2%) seek medical and professional help.

Menopause is not perceived as bothersome by the participants as other women
from other countries. Although it was also found that the symptoms of menopause
increase as they age, almost all of the participants only practice self-care activities and
very few seek professional help making them vulnerable to various complications. Thus,
if menopause-related health services, such as consultations, health education, and
counseling, made available and accessible to women undergoing the transition, a higher
level of wellness is achieved and complications can be prevented.
Accomplishment report (In partial fulfillment of the requirements for N121.2: Intensive Nursing Experience) -- University of the Philippines Manila, June 2018.
Keywords: Intensive community experience